2010
DOI: 10.5664/jcsm.27825
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Acute Physical Exercise on Patients with Chronic Primary Insomnia

Abstract: Study Objectives:The aim was to assess and to compare the acute effects of three different modalities of physical exercise on sleep pattern of patients with chronic primary insomnia. Methods: Forty-eight insomnia patients, 38 female (mean age 44.4 ± 8 y) were randomly assigned to 4 groups: control (CTR, n = 12), moderate-intensity aerobic exercise (MAE, n = 12), high-intensity aerobic exercise (HAE, n = 12), and moderate-intensity resistance exercise (MRE, n = 12). The patients were assessed on sleep pattern (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
100
1
4

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 143 publications
(110 citation statements)
references
References 28 publications
5
100
1
4
Order By: Relevance
“…It is important to note that the participants in this study were good sleepers, which was confirmed by clinical evaluation by the PSQI and night PSG. Studies with subjects reporting poor sleep quality and sleep problems (Esteves, de Mello, Pradella-Hallinan, & Tufik, 2009;Passos et al, 2010;Passos, Tufik, Santana, Poyares, & Mello, 2007;Tanaka et al, 2001) as well as elderly participants (King, Oman, Brassington, Bliwise, & Haskell, 1997) have demonstrated significant effects on sleep pattern resulting from exercise. Youngstedt (2005) states that including only good sleepers in the experiment may not result in any significant changes because there is little room for improvement in the sleep pattern of the subjects, referred to as ceiling and floor effects.…”
Section: Discussionmentioning
confidence: 99%
“…It is important to note that the participants in this study were good sleepers, which was confirmed by clinical evaluation by the PSQI and night PSG. Studies with subjects reporting poor sleep quality and sleep problems (Esteves, de Mello, Pradella-Hallinan, & Tufik, 2009;Passos et al, 2010;Passos, Tufik, Santana, Poyares, & Mello, 2007;Tanaka et al, 2001) as well as elderly participants (King, Oman, Brassington, Bliwise, & Haskell, 1997) have demonstrated significant effects on sleep pattern resulting from exercise. Youngstedt (2005) states that including only good sleepers in the experiment may not result in any significant changes because there is little room for improvement in the sleep pattern of the subjects, referred to as ceiling and floor effects.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, insomnia treatment should be aetiological and not merely symptomatic. Cognitive behaviour therapy, which includes appropriate sleep hygiene, limiting time spent in bed, relaxation techniques or physical exercise, should be used, depending on the patient (Harsora and Kessman, 2009;Passos et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, moderate intensity aerobic exercise reduced sleep onset latency and total wake time after sleep onset, and it increased total sleep time and sleep efficiency based on objective polysomnography data. 50 In an older population, Morgan found that higher levels of physical activity were protective against incident and chronic insomnia. 51 However, Youngstedt et al reported no association between self-reported sleep and total daily physical activity among physically active, healthy college volunteers who were mostly good sleepers.…”
Section: Discussionmentioning
confidence: 99%